Promoción del c-learning a través del uso de herramientas, software y entornos virtuales - Castillo Rodríguez, Cristina; Rios Moyano, Sonia (Historia y Comunicación Social, 2017)
Collaboration in the teaching-learning process has increased more and more in the education environment. Besides, technologies in general have become part of our daily lives in such a way that we cannot conceive certain domains of knowledge without them, like the field of education. In this paper a classification of certain tools and environments will be proposed so as to promote the acquisition of contents related to subjects of several disciplines as well as to foster a collaborative learning.
Fostering c-learning through the use of virtual tools, software and environments
La colaboración en el aprendizaje es una tendencia que impera actualmente en el entorno educativo. Además, la tecnología en general ha pasado a formar parte de nuestra vida cotidiana de tal forma que no podemos concebir determinados dominios del conocimiento sin su uso, como el ámbito de la educación. En este artículo se ofrece una clasificación de herramientas y entornos virtuales para promover la adquisición de contenidos de varias disciplinas y para fomentar un aprendizaje colaborativo.
Keywords: TIC; TAC; entornos y plataformas virtuales; educación superior; c-learning; e-learning; ICT; LKT; virtual platforms and environments; higher education; WOS; Scopus